ChemInform Abstract: 2‐Substituted 3‐Arylindoles Through Palladium‐Catalyzed Arylative Cyclization of 2‐Alkynyltrifluoroacetanilides with Arylboronic Acids under Oxidative Conditions. Issue 22 (13th May 2013) - Arcadi, Antonio; Cacchi, Sandro; Fabrizi, Giancarlo; Goggiamani, Antonella; Iazzetti, Antonia; Marinelli, Fabio
Abstract An efficient, new and alternative approach for the synthesis of various substituted indoles has been developed.